Modelling heat transfer in permafrost with COMSOL - Korhonen, Vesa (Helsingin yliopisto, 2023)
Thawing of permafrost is widely observed, and its rate is expected to be accelerated due to the global warming caused by anthropogenic climate change. Although permafrost thawing has been acknowledged in IPCC Assessment reports, uncertainties related to model-based estimates of its extent and magnitude in the future exist due to the challenges for the models to account for heterogeneous changes in permafrost under the changing climate. Various one-dimensional finite element conductive heat transfer model codes have been successfully used for simulating permafrost, while models created with the COMSOL multiphysics tool have seen little use. In this work, COMSOL version 5.6 was chosen for modelling the heat transfer in permafrost. COMSOLs' ability to accurately simulate thermal evolution in porous medium experiencing freezing was demonstrated using the Interfrost test case T1, which is a benchmark modelling problem adapted to use by the Intercomparison project for TH (Thermo-Hydro) coupled heat and water transfers in permafrost regions. Benchmark results agreed with Lunardini's analytical solution, although compared to the previous studies, the results had more deviation from the analytical solution. Discontinuous permafrost in North-Western Siberia is thawing. Based on the temperature measurements available from three boreholes located in the area (Nadym), and an observed increasing mean annual air temperature trend of 0.5° C per decade, the rate of thawing could be increasing. A one-dimensional heat transfer model for one of the boreholes was created and benchmarked against soil temperature measurements to form a basis for future estimates of the permafrost evolution. The temperature time series produced by the model agreed moderately with the measurements, but the need for further model improvements was identified. Adjustments proposed in this work and parameter changes indicated by the sensitivity analysis form a basis for further model development. Additionally, the results of the conducted ...